Learning Effectiveness in Year-Round Hajj Manasik Guidance: A Case Study in Gowa Regency, South Sulawesi - Sri Ilham Lubis (Mimbar Agama Budaya, 2025)
This study addresses the limited effectiveness of conventional, ten-session, lecture-centric Hajj Manasik for pilgrims of diverse ages and schooling by evaluating a year-round manasik program at KUA Somba Opu (Gowa). Methods used a descriptive design combining observation, interviews, and pre–post questionnaires in 2022 with 107 participants (of 163) and 15 instructors; measures covered understanding of pillars, obligations, procedures, and timing, plus perceived benefits and barriers through an andragogical lens. The Results of this study show comprehension rose markedly. "Novice" fell from 47% to 17.5% and "limited" from 30% to 11.7%, while "good" increased from 14% to 49% and "ready/independent" from 7% to 22%. The most effective formats were field practice (ṭawāf, sa'i, ramy al-jamarāt), cohort-based learning, and guided Q&A; Pure lectures performed weakest. Barriers included uneven instructor qualifications, budget constraints, inadequate teaching aids, and thin coverage of end-to-end travel. The program effectively builds competence; we recommend standardized curricula, instructor recruitment and training, upgraded facilities, and wider implementation across KUAs.